INFLUENCE OF ANTIBODIES AGAINST CTLA-4 AND PD-1 UPON QUANTITIES OF THEIR TARGET RECEPTORS - I. O. Chikileva (Medicinskaâ Immunologiâ, 2019)
Inhibitory receptors CTLA-4 and PD-1 (immune checkpoints) play a key role in regulation of immune reactions. They suppress excessive immune response against pathogenic microbes and prevent autoimmune reactions. The immune checkpoints are targets of the modern effective therapy based on human and humanized monoclonal antibodies (ipilimumab and nivolumab, tremelimumab, pembrolizumab, etc). However, despite its high efficiency compared to standard chemotherapy, the therapy based on blocking immune check points is facing several problems, i.e., high therapy cost and severe negative autoimmune-related side effects. Unfortunately, this therapy helps to minority of the patients. Hence, further studies are required to improve its efficiency and safety, as well as to search for selection criteria of the patients who would benefit from the therapy. An appealing approach to reduce negative side effects from immune checkpoint inhibition is application of the blocking antibodies, aiming for ex vivo generation of patients’ activated immune cells for cancer therapy, thus avoiding systemic drug administration. Our aim was to elucidate influence of immune checkpoint blocking antibodies on the expression of CTLA-4 and PD-1 in such an in vitro model. First of all, we have determined quantities of lymphocyte receptors in peripheral blood of healthy volunteers, or cancer patients with disseminated melanoma. Moreover, we defined effect from the addition of antibodies against immune checkpoints on proportions of cells expressing CTLA-4 and PD-1 in the population of phytohemagglutininactivated lymphocytes. Our study demonstrated that, in presence of antibodies to either of the two checkpoints during in vitro cell activation, the blockade of specific target receptor is accompanied by reduced number of cells positive for another checkpoint. Hence, the antibodies directed against PD-1 or CTLA-4 seem to suppress both negative signal cascades at once, if tested under such experimental conditions. Noteworthy, the response to blocking antibodies for different immune checkpoints varied for different donors. Our data may be used for development of effective combinations of lymphocyte activators and immune check-point inhibitors, for in vitro generation of activated lymphocytes applied for adoptive cancer therapy, as well as for prediction of possible responses to antibodies against CTLA-4 or PD-1, aiming to select the best personalized cancer immunotherapy.